Manajemen Bimbingan Muallaf Lembaga Dakwah Ibadah Pemakmuran Masjid (LDIPM) Yayasan Mu-Ahidin Kalimantan Barat - Wulandari, Poppy Ferbianti; Patmawati; Waldan, Raziki (Program Studi Bimbingan dan Konseling Islam, 2023)
The purpose of this study was to find out more information related to: (1) Planning for Guidance for Muallaf LDIPM Mujahidin Foundation of West Kalimantan; (2) Organizing the Muallaf Guidance of the LDIPM Mujahidin Foundation in West Kalimantan; (3) Implementation of Muallaf Guidance of LDIPM Mujahidin Foundation of West Kalimantan; and (4) Supervision of Muallaf Guidance of LDIPM Mujahidin Foundation of West Kalimantan.This research includes qualitative research. Sources of data from this research are from the relevant respondents, such as the Executive Director of the Mujahidin Foundation, the Head of the institution, the Secretary of the Institution, the Staff of the Institution and the Coordinator of the Trustees. The technique used for data collection is a direct communication technique using interview guides, observation guidelines and documentation guidelines. Meanwhile, to analyze the data, the researcher used interactive model analysis.Based on the analysis carried out, the researchers concluded that: 1) The planning for the guidance of converts to converts carried out by LDIPM can be seen from the things that have been prepared by the institution for converts, such as providing pre-converting consultation services and facilitating the needs of converts; 2) Organizing the guidance of LDIPM converts can be seen from the management carrying out their roles and functions according to the existing organizational structure; 3) The implementation of guidance for LDIPM converts can be seen when the coaches run their programs, such as daily guidance activities, monthly routine activities on the last Friday of the month and annual activities for distributing basic necessities to converts in the holy month of Ramadan; 4) Supervision of the guidance of LDIPM converts can be seen in the head of the institution carrying out supervision when needed only by telephone or monitoring once a week to come to the institution.